Research and realization on USBKEY based network storage user data protection - Xiao YU; Li TIAN; Zhe LIU; Jie WANG (网络与信息安全学报)
Network storage services such as network hard disk and cloud storage are widely used.However,due to the relative flexibility of network hard disk and cloud storage,it has to face many security risks.Based on the data encryption protection mechanism of USBKEY,data encryption and storage service,the key is stored in USBKEY,will eventually “service level provide security” elaboration to the ＆quot;real master security＆quot; to achieve the purpose of user control of data security.